Peroxiredoxin-2 and STAT3 form a redox relay for H2O2 signaling - Sobotta, Mirko Christoph; Liou, Willy; Stöcker, Sarah; Talwar, Deepti; Oehler, Michael; Ruppert, Thomas; Scharf, Annette N. D.; Dick, Tobias P. (Nature chemical biology, 2015)
A redox relay was identified in mammalian cells where the H2O2-reactive protein peroxiredoxin-2 oxidizes the transcription factor STAT3, resulting in the formation of transcriptionally inactive disulfide-linked oligomers.
Published online: 24 november 2014
Gesehen am 18.06.2020
Im Titel ist "2" in H2O2 tiefgestellt